Hexagonal boron nitride-guanazole-sodium hexametaphosphate flame-retardant resin coating and preparation method thereof
By combining hexagonal boron nitride with guanidazole and sodium hexametaphosphate, the problems of poor dispersion of existing flame retardants and low residual carbon amount are solved, and efficient smoke reduction and flame retardant performance are achieved.
Patent Information
- Application Number
- CN202411724971.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing flame retardant based on hexagonal boron nitride has problems such as poor dispersion and low residual carbon content, resulting in large smoke release and poor flame retardant performance.
By combining hexagonal boron nitride with guanazole and sodium hexametaphosphate, guanazole is used as a surface aminating agent and nitrogen source, and sodium hexametaphosphate is used as a physical crosslinking agent and a phosphorylation treatment agent, combined with ultrasonic treatment, the dispersion and flame retardant properties of hexagonal boron nitride are improved.
The flame retardant performance of the flame retardant resin coating is significantly improved, forming a dense carbon residue carbon layer, reducing the smoke release amount and heat release rate, and improving the carbon residue and thermal stability of the material.
Smart Images

Figure CN119552551A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of flame retardant materials, and in particular to a hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating and a preparation method thereof. Background Art
[0002] Wood is an abundant and sustainable biomass material. It is widely used in various fields due to its low cost and excellent mechanical properties. However, wood is easy to catch fire and releases a lot of smoke, which brings great harm to people. Therefore, we need to improve the flame retardant properties of wood. There are two main methods to reduce the flame retardant properties of wood, coating wood flame retardant coatings and wood impregnation solutions. Wood flame retardant coatings usually use compounds containing halogens, boron, phosphorus, nitrogen and inorganic metals (such as aluminum, magnesium and zinc) to improve the flame retardancy of wood. For example, the inventor of the present invention has made preliminary research results, and the existing document 1 (application number: 2024113226527. Preparation and application of urea-formaldehyde resin blended guanazole-phytic acid copper flame retardant resin coating) uses guanazole, phytic acid, copper hydroxide, formaldehyde and urea as raw materials, and prepares urea-formaldehyde resin blended guanazole-phytic acid-copper flame retardant resin coating by chemical reaction and physical blending. The purpose of the invention of this technical solution is to improve the density of the carbon layer of the flame retardant matrix, reduce the heat release and the total heat release, therefore, metallic copper is introduced through a complex reaction to synthesize a guanazole-copper phytate flame retardant, and then blended with urea-formaldehyde resin to form a flame retardant coating. Although this technical solution utilizes the characteristics of metallic copper catalytic degradation of resin to promote the formation of a dense residual carbon layer, solving the problems of carbon layer density and heat release, the characteristics of metallic copper catalytic degradation of resin will also lead to a decrease in the degradation temperature of the resin, that is, a decrease in the thermal stability of the resin. This problem is not only reflected in the decomposition temperature, but also in the low effect of improving the residual carbon amount and carbonization rate.
[0003] In order to solve the problem of low carbonization rate mentioned above, components with high thermal conductivity can be introduced to improve the carbonization rate, thermal stability and thermal conductivity of the polymer matrix. For example, existing document 2 (Improving fire safety and mechanical properties of waterborne polyurethane by montmorillonite-passivated black phosphorus [J]. Chemical Engineering Journal, 2023, 464: 142683.) uses hexagonal boron nitride, chitosan and polyvinyl alcohol as raw materials to prepare a flame retardant by magnetic stirring, which is applied on the surface of wood to form a flame retardant film. The results of the combustion test show that the carbonization rate of the flame retardant is 61.3%. This technical solution introduces hexagonal boron nitride and utilizes the high thermal stability and high thermal conductivity of hexagonal boron nitride itself to improve the thermal stability and carbonization rate of the flame retardant system. The principle is that the residual carbon amount of the flame retardant material is positively correlated with the initial carbonization, that is, increasing the initial carbonization temperature can increase the carbonization rate. Due to the above reasons, the total heat release THR of this technical solution is only reduced by 7.54%. However, the smoke release rate of this technical solution not only did not decrease, but increased by 55.56%. Further analysis shows that the main reason for smoke release is that polyvinyl alcohol is used as a film-forming material in the raw materials of this technical solution, and polyvinyl alcohol will release a large amount of smoke when it burns in the presence of an open flame. This technical solution also has the problem that hexagonal boron nitride is not easy to disperse evenly in an aqueous solution due to its chemical inertness.
[0004] In order to solve the problem of large amount of smoke, the prior art adopts the preparation of gel flame retardant instead of film flame retardant, avoiding the use of film-forming materials represented by polyvinyl alcohol; at the same time, in order to solve the problem of hexagonal boron nitride, the method of modifying hexagonal boron nitride can be used to improve the dispersibility. For example, existing document 3 (Zinc ion cross-linked sodiumalginate modified hexagonal boron nitride to enhance the flame retardant properties of composite coatings [J]. Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2022, 647: 129200) First, through the interaction of Lewis acid and base and ultrasonic treatment, water-soluble polyethyleneimine is loaded on hexagonal boron nitride nanosheets to achieve the modification of hexagonal boron nitride, and then sodium alginate is added to prepare a gel-type flame retardant. The residual carbon rate of the flame retardant obtained by this technical solution can reach 31.7%, and the smoke density level SDR is reduced from 63.5% to 41.2%, a reduction of 35.12%. This technical solution avoids the use of raw materials that produce a lot of smoke, but since the obtained material is a gel, it directly leads to two technical problems: 1. The modified hexagonal boron nitride still exists in the form of nanoparticles and cannot be evenly dispersed in the gel; 2. The residual carbon layer formed by the gel during the combustion process must have a small amount of pores or even cracks.
[0005] The method for solving the dispersibility of hexagonal boron nitride can be to improve the dispersibility of hexagonal boron nitride by using an organic solvent while modifying hexagonal boron nitride. For example, in existing document 4 (Thermal exfoliation of hexagonal boron nitride for effective enhancements on thermal stability, flame retardancy and smoke suppression of epoxy resin nanocomposites via sol-gel process [J]. Journal of Materials Chemistry A, 2016, 4 (19): 7330-40), first, the method of heat treatment, the hexagonal boron nitride BN is modified to hydroxylated hexagonal boron nitride BNO, then, acetone is used as a solvent to improve the dispersibility of BNO, and at the same time, the epoxy resin EP is modified by (triisocyanate propyl) triethoxysilane to obtain a silane-modified epoxy resin MEP, and finally, BNO, MEP and dibutyltin dilaurate are compounded to prepare a flame retardant. Among them, between BNO and MEP, covalent bonding is carried out by a functional group represented by a hydroxyl group to improve dispersibility and stability. The technical effect of reducing PHRR and THR by 53.1% and 32.6% respectively and reducing the total smoke release by 23.13% was obtained, but the carbon residue was only 22.4%. The reason for this is that the problem with this technical solution is that BNO itself has a low carbon content, which means that the carbon residue cannot be directly increased. Therefore, using BNO alone as a flame retardant additive has the problem of low carbon residue. Summary of the invention
[0006] The purpose of the present invention is to provide a hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating and a preparation method thereof.
[0007] In view of the problem that the flame retardant based on hexagonal boron nitride in the prior art needs to be treated for activation and the amount of residual carbon is increased, the problem is solved by compounding hexagonal boron nitride BN with 3,5-diamino-1,2,4-triazole GZ and sodium hexametaphosphate SHMP. Specifically, guanazole GZ is used as a surface amination treatment agent and nitrogen source, SHMP is used as a physical crosslinking agent, phosphating treatment agent and acid source, and ultrasonic treatment is combined to improve the dispersibility of BN, and finally improve the flame retardant properties of the flame retardant resin coating.
[0008] In order to achieve the above invention object, the technical solution adopted by the present invention is:
[0009] A hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating, which is prepared from hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant BNGS, urea and formaldehyde as main raw materials, dioctyl phthalate DOP as plasticizer, and tannic acid TA as curing agent, through four-stage reaction, to obtain hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating UF-BNGS;
[0010] The BNGS is prepared by chemical reaction using hexagonal boron nitride BN, 3,5-diamino-1,2,4-triazole GZ and sodium hexametaphosphate SHMP as bio-based flame retardant ingredients as raw materials;
[0011] The obtained BNGS contains BN, PNC, POP, P=O, -NH2 and OH;
[0012] The temperature at which the UF-BNGS decomposes to 5% by mass is 228.90±1.10°C, the temperature at which the maximum decomposition rate is reached is 301.47±1.50°C, and the residual carbon content at 800.00°C is 39.95±0.50wt.%;
[0013] When the addition amount of BNGS is 2wt.%, a dense residual carbon layer is formed.
[0014] A method for preparing a hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating comprises the following steps:
[0015] Step 1, preparation of hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant, first, hexagonal boron nitride BN is placed in water, and ultrasonically dispersed under certain conditions to obtain a BN solution, then guanazole GZ is placed in the BN solution, and stirred in a water bath under certain conditions to obtain an amino-functionalized BN-GZ solution, then sodium hexametaphosphate SHMP is placed in the BN-GZ solution, and stirred under certain conditions to obtain a BNGS solution, and after the reaction is completed, the obtained product is filtered, washed, dried, and ground into powder to obtain the hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant BNGS;
[0016] In the step 1, the mass ratio of BN, GZ and SHMP is 1:1:2;
[0017] In the step 1, the ultrasonic condition is that the ultrasonic time is 1h;
[0018] In step 1, the conditions for water bath stirring are: water bath temperature is 60-70° C., stirring speed is 400-500 rpm, and stirring time is 1-1.5 h;
[0019] In step 1, the stirring reaction conditions are: the reaction temperature is 90° C. and the reaction time is 3 h;
[0020] In the step 1, the washing is completed under the condition that the pH of the washing solution is 6-7; the drying conditions are that the drying temperature is 80° C. and the drying time is 24 hours;
[0021] Step 2, preparation of hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating, first, sodium hydroxide solution is added to formaldehyde solution, pH value of the solution is adjusted to obtain solution A, then, under certain conditions, urea, BNGS and other raw materials are added in four stages to prepare urea-formaldehyde resin blended hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating UF-BNGS;
[0022] In the step 2, the mass ratio of the total added amount of BNGS, formaldehyde and urea obtained in step 1 is 2:100:57;
[0023] In step 2, the conditions for preparing solution A are to adjust the pH value of the solution to 8.0-8.5;
[0024] In step 2, the conditions for adding urea are: a stirring speed of 400-500 rpm and a reaction temperature of 90° C.;
[0025] In step 2, the four stages of adding urea are specifically:
[0026] Step 2.1 is to add the first stage urea under a certain temperature condition, and continue stirring for a certain stirring time after the addition is completed;
[0027] In the step 2.1, the amount of urea added is 64.9% of the total amount of urea, the temperature in step 2.1 is 90° C., and the stirring time is continued for 30 minutes;
[0028] Step 2.2 is, under a certain temperature condition, first adding acetic acid solution to adjust the pH value of the solution, then adding the second stage urea, and after the addition is completed, continuing stirring for a certain stirring time until the reaction end point is reached;
[0029] In the step 2.2, the amount of urea added is 21.6% of the total amount of urea, the pH value of the solution is adjusted to 4.5-5.0, the temperature of step 2.2 is 90° C., and the stirring time is continued for 15 minutes;
[0030] The endpoint of the second stage reaction is determined by the following sign: a drop of the solution is dropped into 30°C water, and the dropped solution condenses in the water without dispersing;
[0031] Step 2.3 is to first add sodium hydroxide solution to adjust the pH value under a certain temperature condition, and then add urea from the third stage. After the addition is completed, stir until it becomes viscous to obtain UF;
[0032] In the step 2.3, the amount of urea added is 13.3% of the total amount of urea, the pH value of the solution is adjusted to 7.5-8.0, the temperature of step 2.2 is 90° C. when adjusting the pH value, and after the pH value is adjusted, the temperature is adjusted to 70° C., and the stirring time is 30-40 min;
[0033] Step 2.4 is to add BNGS to UF and stir it under certain conditions to obtain UF-BNGS;
[0034] In step 2.4, the stirring rate for adding BNGS is 400 rpm, and the stirring temperature is room temperature.
[0035] A hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating, when used as a wood flame retardant coating, has flame retardant properties and can form a continuous and dense residual carbon layer after combustion; in the UL-94 grade test, it passes the UL-94V-0 grade test; in the cone calorimetry test, the heat release rate HRR is 55.73±1.25kW / m 2 .
[0036] The technical effect of the hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating obtained by the present invention is tested as follows:
[0037] The TG test results show that when the decomposition mass of UF-BNGS-2 is 5%, the temperature is 228.90±1.10℃, the temperature when the maximum decomposition rate is reached is 301.47±1.50℃, and the residual carbon amount at 800.00℃ is 39.95±0.50wt.%; coating UF-BNGS-2 can increase the residual carbon rate of the material and produce a more stable residual carbon layer in the high temperature area.
[0038] The expanded carbon layer formed on the surface of NW coated with UF-BNGS-2 flame retardant coating after combustion was further tested by SEM. UF-BNGS-2 can form a dense carbon layer with almost no holes. The test results show that UF-BNGS-2 can form a high-quality residual carbon layer after combustion, which can isolate oxygen and heat, thereby improving the flame retardant properties of NW.
[0039] The vertical burning test showed that coating with UF-BNGS-2 flame retardant coating enabled NW to pass the UL-94V-0 rating.
[0040] The limiting oxygen index test shows that coating UF-BNGS-2 flame retardant coating can improve its limiting oxygen index, LOI reaching 34.0%.
[0041] The results of cone calorimetry tests show that the heat release rate of wood coated with UF-BNGS-2 flame retardant coating is 55.73±1.25%, which can significantly reduce the heat release rate of NW.
[0042] Therefore, the present invention has the following advantages over the prior art:
[0043] 1. The bio-based flame retardant resin coating of the present invention increases the residual carbon content of the substrate by hexagonal boron nitride, and at the same time obtains a significant improvement in flame retardancy, wherein sodium hexametaphosphate is decomposed into pyrophosphate by heat, which can not only promote carbonization of the substrate, but also increase the formation of coke and increase the residual carbon content;
[0044] 2. The present invention improves the activity of hexagonal boron nitride by subjecting hexagonal boron nitride to an amination treatment and introducing sodium hexametaphosphate as a physical crosslinking agent for phosphorylation treatment;
[0045] 3. The raw materials involved in the present invention are all commercially available and are low-cost raw materials, that is, they meet the application requirements of large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 is the FTIR graph of Example 1;
[0047] Figure 2 FTIR images of Example 1 and Comparative Example 2;
[0048] Figure 3 TG diagrams of Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4;
[0049] Figure 4 is the SEM image of Example 1;
[0050] Figure 5 It is a vertical combustion test diagram of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4;
[0051] Figure 6 It is the HRR diagram of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4;
[0052] Figure 7 It is the SEM picture of comparative example 1;
[0053] Figure 8 It is the SEM picture of comparative example 2;
[0054] Fig. 9 It is the SEM picture of comparative example 3;
[0055] Fig.10 It is the SEM picture of comparative example 4;
[0056] Fig.11This is the SEM image of Comparative Example 5. DETAILED DESCRIPTION
[0057] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0058] Example 1
[0059] A method for preparing a hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating comprises the following steps:
[0060] Step 1, preparation of hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant BNGS, first, 2g of hexagonal boron nitride BN is placed in 150mL of water, and ultrasonic dispersion is performed for 1h to obtain a BN solution, then 9.71g of guanazole GZ is placed in the BN solution, and stirred in a water bath at a water bath temperature of 70°C, a stirring speed of 400rpm, and a stirring time of 1h to obtain an amino-functionalized BN-GZ solution, then 10g of sodium hexametaphosphate SHMP is placed in the BN-GZ solution, and stirred at a reaction temperature of 90°C and a reaction time of 3h to obtain a BNGS solution, and after the reaction is completed, the obtained product is filtered, washed, dried, and ground into powder to obtain a hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant, referred to as BNGS;
[0061] The washing is completed under the condition that the pH of the washing liquid is 6-7; the drying conditions are that the drying temperature is 80° C. and the drying time is 24 hours;
[0062] In order to prove the composition of BNGS, i.e. successful synthesis, FTIR test was performed. The test results are as follows Figure 1 As shown, BNGS contains characteristic peaks of -NH, P=O, PNC / BN and POP at the same time, among which the characteristic peak of -NH belongs to GZ, the characteristic peaks of P=O and POP belong to SHMP, PNC belongs to the mixture of GZ and SHMP, and BN belongs to BN and amino-functionalized BN. The test results show that the BNGS flame retardant was successfully synthesized.
[0063] Step 2, preparation of hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating UF-BNGS, first, 20wt.% sodium hydroxide solution is added to 100g 37wt.% formaldehyde solution, and the pH value of the solution is adjusted to 8.0-8.5 to obtain solution A, then, under the conditions of a stirring speed of 400rpm and a reaction temperature of 90°C, the BNGS obtained in step 1, urea and other raw materials are added in four stages,
[0064] Among them, the addition amount of BNGS is 2wt.% of UF, specifically 2g, and the total addition amount of urea is 57%, specifically 57g;
[0065] The urea-formaldehyde resin-blended hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating, referred to as UF-BNGS-2, can be prepared.
[0066] The four stages are:
[0067] Step 2.1 is to add 37 g of the first-stage urea while maintaining the temperature at 90°C. After the addition is completed, continue stirring for 30 minutes;
[0068] Step 2.2 is to add 20 wt.% acetic acid solution at 90°C, adjust the pH value of the solution to 4.5-5.0, and then add 12.4 g of the second stage urea. After the addition is completed, continue stirring for 15 minutes until the reaction end point is reached;
[0069] The endpoint of the second stage reaction is determined by the following sign: a drop of the solution is dropped into 30°C water, and the dropped solution condenses in the water without dispersing;
[0070] Step 2.3 is to add 20wt.% sodium hydroxide solution while maintaining the temperature at 90°C, adjust the pH value to 7.5-8.0, and then add 7.6g of urea from the third stage. After the addition is completed, adjust the temperature and stir at a stirring temperature of 70°C for 30 minutes to obtain UF;
[0071] Step 2.4 is to add 2 g of BNGS to UF, and stir at room temperature at a stirring rate of 400 rpm and a stirring time of 30 min to obtain UF-BNGS. The UF-BNGS-2 mixed emulsion obtained in specific Example 1 is named UF-BNGS-2.
[0072] Since the subsequent tests need to be carried out after the UF-BNGS-2 is cured, a specific curing method is provided. The curing method is, first, under the conditions of a stirring rate of 400 rpm and a stirring time of 30 min, dioctyl phthalate DOP, tannic acid TA and UF-BNGS-2 meet the mass ratio of 0.1:0.1:10, that is, 1g DOP and 1g TA are added to 100g UF-BNGS-2 to obtain UF-BNGS-2 flame retardant resin coating, and then, according to experimental needs, the UF-BNGS-2 flame retardant resin coating is placed in a mold for direct curing or applied to the wood surface, and cured for 72 h to obtain a BNGS-based flame retardant resin coating. Since there is no need to distinguish, the cured material is still referred to as UF-BNGS-2;
[0073] The specific method for coating the wood surface is to evenly coat UF-BNGS-2 on the wood surface with a coating thickness of 0.3 mm, and then dry it for 24 h after coating.
[0074] In order to prove the composition of UF-BNGS-2, i.e., successful synthesis, FTIR test was performed. The FTIR test results are shown in Figure 2 As shown, UF-BNGS-2 contains characteristic peaks of -OH, P=O, OPC, PO-ph, BN and BOC, among which the characteristic peak of -NH2 belongs to GZ, the characteristic peaks of P=O, PO-ph and OPC belong to SHMP, and BN and BOC belong to BN. The test results show that the UF-BNGS-2 flame retardant coating is composed of GZ, SHMP and BN, that is, UF-BNGS-2 is successfully synthesized.
[0075] In order to prove the technical effect of UF-BNGS-2 as a wood flame retardant coating, TG test was carried out. The test results are as follows Figure 3 As shown in Table 1, the temperature when the decomposition mass of UF-BNGS was 5% was 228.90±1.10°C, the temperature when the maximum decomposition rate was reached was 301.47±1.50°C, and the residual carbon amount at 800.00°C was 39.95±0.50wt.%.
[0076] Table 1 Summary of TG test results
[0077]
[0078] In order to further verify the microscopic morphology of the residual carbon layer, SEM test was performed on the surface of UF-BNGS-2 after TG test. Figure 4 As shown in the figure, UF-BNGS-2 can form a dense carbon residue layer with almost no holes, which is referred to as a dense structure. The test results show that UF-BNGS-2 can form a high-quality carbon residue layer after combustion, which can isolate oxygen and heat, thereby improving the flame retardant properties of wood.
[0079] In order to further demonstrate the flame retardancy of UF-BNGS-2, vertical burning test and limiting oxygen index test were performed.
[0080] Vertical burning test results are as follows Figure 5 As shown in Table 2, the open flame time of UF-BNGS-2 after the first ignition was 1.0s, and the open flame and flameless combustion time after the second ignition was 1.7s, with no dripping, indicating that UF-BNGS-2 passed the UL-94 V-0 grade;
[0081] The limiting oxygen index test results are shown in Table 2. The limiting oxygen index of UF-BNGS-2 is 34.0%.
[0082] Table 2 Vertical combustion test and oxygen index test results
[0083]
[0084] To further quantify the flame retardancy of UF-BNGS-2, cone calorimetry tests were performed. Figure 6 As shown, the heat release rate HRR of UF-BNGS-2 is 55.73kW / m 2 .
[0085] In order to demonstrate the effect of UF-BNGS-2 on the flame retardant properties of wood, comparative example 1 is provided, wood without flame retardant coating is used as a basic reference sample, and comparative example 2 is provided, pure urea-formaldehyde resin UF without adding BNGS-2 flame retardant.
[0086] Comparative Example 1
[0087] A type of wood that is not coated with flame retardant, referred to as NW.
[0088] In order to verify the microstructure of the residual carbon layer, SEM test was performed on the NW after complete combustion. Figure 7 As shown, the carbon layer after burning NW is almost completely broken, referred to as broken structure. Compared with Example 1, coating UF-BNGS-2 can form a dense carbon residue layer, that is, improve the flame retardant performance.
[0089] To further demonstrate the flame retardancy of NW, vertical burning test and limiting oxygen index test were performed.
[0090] Vertical burning test results are as follows Figure 5 As shown in Table 2, the open flame time of NW after the first ignition is greater than 60s, and there is dripping, which indicates that NW does not pass the UL-94 V-0 grade. Compared with Example 1, it can be seen that coating UF-BNGS-2 can make NW pass the UL-94 grade test.
[0091] The limiting oxygen index test results are shown in Table 2. The limiting oxygen index of NW is 20.3%. Compared with Example 1, it can be seen that coating UF-BNGS-2 can increase the limiting oxygen index from 20.0% to 34.0%.
[0092] To further quantify the flame retardancy of NWs, cone calorimetry tests were performed. Figure 6 As shown, the HRR of NW is 232.22kW / m 2Compared with Example 1, it can be seen that coating UF-BNGS-2 can reduce the HRR by 76.00%, that is, significantly reduce the heat release rate, thereby significantly improving the flame retardancy.
[0093] Comparative Example 2
[0094] A method for preparing pure urea-formaldehyde resin UF without adding BNGS flame retardant, wherein the steps not specifically stated are the same as those in Example 1, except that: step 1 is not required, and in step 2, step 2.2 does not add BNGS, so that pure urea-formaldehyde resin UF without adding BNGS flame retardant can be obtained, which is referred to as UF for short.
[0095] In order to prove the technical effect of UF as a wood flame retardant coating, TG test was carried out. The test results are as follows Figure 3 As shown in Table 1, the temperature at which the UF decomposition mass is 5% is 204.2°C, the temperature at which the maximum decomposition rate is reached is 300.32°C, and the amount of residual carbon at 800°C is 10.00wt.%. Compared with Example 1, the addition of UF-BNGS can increase the amount of residual carbon from 10.00wt.% to 39.94wt.%, an increase of 74.96%, that is, the addition of UF-BNGS-2 can significantly increase the amount of residual carbon.
[0096] In order to further verify the microscopic morphology of the residual carbon layer, SEM test was performed on the UF surface after TG test. Figure 8 As shown in the figure, the residual carbon layer formed after the combustion of UF has serious fragmentation, that is, a fragmented structure.
[0097] Compared with Comparative Example 1, it can be seen that although coating with UF can slightly reduce the degree of fragmentation of the residual carbon layer and slightly improve the flame retardancy, the residual carbon layer formed has no substantial change compared with NW and is also a fragmented structure;
[0098] Compared with Example 1, it can be seen that adding the BNGS-2 flame retardant can transform the residual carbon layer from a broken structure to a dense structure.
[0099] In order to further prove the flame retardancy of UF, vertical burning test and limiting oxygen index test were performed.
[0100] Vertical burning test results are as follows Figure 5 As shown in Table 2, the open flame time after the first ignition of UF is 14.2s, and the open flame and flameless combustion time after the second ignition is 16.6s, with no dripping, indicating that UF passes the UL-94V-1 grade.
[0101] Compared with Comparative Example 1, it can be seen that coating with UF can improve the NW from no grade to UL-94V-1 grade, that is, coating with UF can improve the flame retardancy;
[0102] Compared with Example 1, it can be seen that adding BNGS flame retardant can improve the UL-94 grade from V-1 to V-0.
[0103] The limiting oxygen index test results are shown in Table 2. The limiting oxygen index of UF is 27.8%.
[0104] Compared with Comparative Example 1, it can be seen that coating with UF can increase the limiting oxygen index from 20.0% to 27.8%, that is, coating with UF can improve the flame retardancy;
[0105] Compared with Example 1, it can be seen that adding BNGS flame retardant can increase the limiting oxygen index from 27.8% to 34.0%.
[0106] To further quantify the flame retardancy of NWs, cone calorimetry tests were performed. Figure 6 As shown, the HRR of UF reaches 87.22kW / m 2 ,
[0107] Compared with comparative example 1, the reduction in HRR achieved by coating with UF is 62.44%, that is, the heat release rate is reduced and the flame retardancy is improved;
[0108] Compared with Example 1, it can be seen that adding BNGS-2 flame retardant can further reduce the HRR amplitude by 36.10%.
[0109] It can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that the reason why coating UF improves the flame retardancy is that UF itself has higher flame retardancy than pure wood. However, only adding UF can only obtain a very low amount of residual carbon, and the formed residual carbon layer is in a broken state, that is, the quality is poor, which makes it impossible to effectively improve the flame retardant performance; while adding BNGS flame retardant can significantly increase the residual carbon amount and form a dense residual carbon layer at the same time, thereby achieving the effect of significantly improving the flame retardancy.
[0110] In order to demonstrate the effect of SHMP on the flame retardant properties of BNGS, that is, its role in the technical solution, comparative example 3 is provided, which is a hexagonal boron nitride-guanazole coating prepared without adding SHMP.
[0111] Comparative Example 3
[0112] A hexagonal boron nitride-guanazole coating prepared without adding SHMP, wherein the steps not specifically stated are the same as those in Example 1, except that: in the step 1, sodium hexametaphosphate is not added, and the obtained material is referred to as BNG, and then in the step 2, BNG is used instead of BNGS, i.e., 2 g of BNG is added, and the obtained material is referred to as UF-BNG.
[0113] In order to prove the technical effect of UF-BNG as a wood flame retardant coating, TG test was carried out. The test results are as follows Fig. 9 As shown in Table 1, the temperature when the decomposition mass of UF-BNG is 5% is 235.38±0.20°C, the temperature when the maximum decomposition rate is reached is 341.28±0.80°C, and the residual carbon amount at 800°C is 26.84±1.01wt.%. Compared with Example 1, it can be seen that the addition of sodium hexametaphosphate SHMP can significantly increase the residual carbon amount. The reason is that SHMP contains a phosphate group, which can promote the carbonization of UF-BNG by forming pyrophosphate when heated, thereby increasing the residual carbon amount.
[0114] In order to demonstrate the effect of the amount of BNGS added on the flame retardant properties, comparative examples 4 and 5 are provided, in which the amount of BNGS added to the UF is 1 wt.% and 3 wt.% of the hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant, respectively.
[0115] Comparative Example 4
[0116] A hexagonal boron nitride-guanidine-sodium hexametaphosphate flame retardant resin coating with a BNGS addition amount of 1 wt.%, wherein the steps not otherwise specified are the same as those of Example 1, except that: in the step 2.4, the amount of BNGS added is 1 wt.%, specifically 1 g of BNGS is added, the flame retardant obtained in step 1 is referred to as BNGS-1, and the material obtained in step 2.4 is referred to as UF-BNGS-1.
[0117] In order to prove the technical effect of UF-BNGS-1 as a wood flame retardant coating, TG test was carried out. The test results are as follows Figure 3 As shown in Table 1, the temperature when the decomposition mass of UF-BNGS was 5% was 204.80±1.20°C, the temperature when the maximum decomposition rate was reached was 300.48±0.98°C, and the residual carbon amount at 800°C was 26.88±2.01wt.%.
[0118] Compared with comparative example 2, it can be seen that when the amount of BNGS added is small, the residual carbon content of UF can also be effectively increased by 62.80%;
[0119] Compared with Example 1, when the addition amount of BNGS reaches 2wt.%, the residual carbon content is further significantly increased by 32.70%;
[0120] The test results show that the amount of BNGS added can significantly affect the amount of residual carbon.
[0121] In order to further verify the microscopic morphology of the residual carbon layer, SEM test was performed on the surface of UF-BNGS-1 after TG test. Fig.10As shown, the residual carbon layer formed by UF-BNGS-1 has many holes, that is, a dense residual carbon layer cannot be formed.
[0122] Compared with Comparative Example 2, it can be seen that when the amount of BNGS added is small, the residual carbon layer can only be transformed from a broken structure to a porous structure;
[0123] Compared with Example 1, it can be seen that when the addition amount of BNGS reaches 2wt.%, the residual carbon layer can be transformed from a porous structure to a dense structure, that is, the quality of the residual carbon layer is improved.
[0124] The test results show that the working principle of BNGS flame retardant is that it fills the carbon layer with a broken structure formed by the combustion of NW through its own carbonization process, thereby forming a dense residual carbon layer; when the amount of BNGS added is small, it cannot be fully filled and can only convert the broken structure into a porous structure, so it cannot form a dense residual carbon layer, that is, it cannot effectively improve the flame retardant properties.
[0125] In order to further demonstrate the flame retardancy of UF-BNGS-1, vertical burning test and limiting oxygen index test were performed.
[0126] Vertical burning test results are as follows Figure 5 As shown in Table 2, the open flame time of UF-BNGS-1 after the first ignition is 1.2s, and the open flame and flameless combustion time after the second ignition is 3.3s, and there is no dripping, which indicates that UF-BNGS-1 passes the UL-94V-0 grade.
[0127] Compared with Comparative Example 1, it can be seen that coating with UF-BNGS-1 can improve the NW from no grade to UL-94V-0 grade, that is, coating with UF-BNGS-1 can significantly improve the flame retardancy;
[0128] Compared with Comparative Example 2, it can be seen that coating and adding a small amount of BNGS can improve the UL-94 grade of UF from V-1 to V-0, that is, when the amount of BNGS added is small, the UL-94 grade can also be effectively improved, which has a substantial impact;
[0129] Compared with Example 1, it can be seen that the coated UF-BNGS-2 and UF-BNGS-1 can pass the UL-94 grade test, which means that the addition amount of flame retardant BNGS has no substantial effect on the UL-94 grade.
[0130] The limiting oxygen index test results are shown in Table 2. The limiting oxygen index of UF-BNGS-1 is 32.0%.
[0131] Compared with comparative example 1, coating with UF-BNGS-1 can effectively improve the limiting oxygen index of NW by 36.56%;
[0132] Compared with comparative example 2, it can be seen that when the amount of BNGS added is small, the limiting oxygen index of UF can be further improved by 13.13%;
[0133] Compared with Example 1, it can be seen that the effect of increasing the amount of BNGS added on the limiting oxygen index is negligible, which means that the amount of BNGS added has no substantial effect on the limiting oxygen index.
[0134] In order to further quantify the flame retardancy of UF-BNGS-1, cone calorimetry tests were performed. The test results are shown in Figure 6 As shown, the HRR of UF-BNGS-1 reaches 58.00kW / m 2 .
[0135] Compared with comparative example 1, coating with UF-BNGS-1 can effectively reduce the HRR of NW by 75.02%;
[0136] Compared with comparative example 2, it can be seen that when the amount of BNGS added is small, the HRR of UF can be further significantly reduced by 33.50%;
[0137] Compared with Example 1, it can be seen that when the amount of BNGS added is increased, the HRR increases slightly by 4.07%.
[0138] It can be seen from Comparative Example 4 that even coating a small amount of UF-BNGS can significantly improve the flame retardant properties of NW, that is, significantly increase the residual carbon amount, UL-94 grade and limiting oxygen index, and reduce HRR. However, when the amount of BNGS added is small, a dense structure of the residual carbon layer cannot be effectively formed.
[0139] Comparative Example 5
[0140] A hexagonal boron nitride-guanidine-sodium hexametaphosphate flame retardant resin coating with a BNGS addition amount of 3wt.%, wherein the steps not otherwise specified are the same as those in Example 1, except that: in the step 2.4, the amount of BNGS added is 3wt.%, specifically 3g of BNGS is added, the flame retardant obtained in step 1 is referred to as BNGS-3, and the material obtained in step 2.4 is referred to as UF-BNGS-3.
[0141] In order to prove the technical effect of UF-BNGS-3 as a wood flame retardant coating, TG test was carried out. The test results are as follows Figure 3 As shown in Table 1, the decomposition temperature of UF-BNGS when decomposing 5% is 192.10° C. The temperature at which the maximum decomposition rate is reached is 295.81° C., and the residual carbon content at 800.00 is 17.72 wt.%.
[0142] Compared with comparative example 2, it can be seen that when the amount of BNGS added is high, the residual carbon content of UF can also be effectively increased by 43.57%;
[0143] Compared with Example 1, when the amount of BNGS added reached 3wt.%, that is, when it was excessive, the amount of residual carbon was significantly reduced, with a reduction of 55.64%.
[0144] The test results show that the amount of BNGS added can significantly affect the amount of residual carbon.
[0145] In order to further prove the microscopic morphology of the residual carbon layer, SEM test was performed on the surface of UF-BNGS-3 after TG test. Fig.11 As shown, the residual carbon layer formed by UF-BNGS-3 has many holes, that is, a dense residual carbon layer cannot be formed.
[0146] Compared with Comparative Example 2, it can be seen that when the amount of BNGS added is high, the residual carbon layer can only be transformed from a broken structure to a porous structure;
[0147] Compared with Example 1, it can be seen that when the BNGS addition amount reaches 3wt.%, that is, when it is excessive, the residual carbon layer with an originally dense structure is converted back into a porous structure.
[0148] The test results show that when the amount of BNGS added is excessive, protrusions are formed on the coating surface due to excessive filling of BNGS, that is, new defects are generated, resulting in the inability to form a dense residual carbon layer, that is, the flame retardant properties cannot be effectively improved.
[0149] In order to further prove the flame retardancy of UF-BNGS-3, vertical burning test and limiting oxygen index test were carried out.
[0150] Vertical burning test results are as follows Figure 5 As shown in Table 2, the open flame time of UF-BNGS-3 after the first ignition is 1.1s, and the open flame and flameless combustion time after the second ignition is 15.0s, and there is no dripping, which indicates that UF-BNGS-3 passes the UL-94V-0 grade.
[0151] Compared with Comparative Example 1, coating with UF-BNGS-3 can improve the NW from no grade to UL-94V-0 grade, that is, coating with UF-BNGS-3 can significantly improve the flame retardancy;
[0152] Compared with Comparative Example 2, it can be seen that coating with excessive BNGS can also improve the UL-94 grade of UF from V-1 to V-0, that is, when the amount of BNGS added is excessive, the UL-94 grade can also be effectively improved, which has a substantial impact;
[0153] Compared with Example 1, it can be seen that the coated UF-BNGS-2 and UF-BNGS-3 can pass the UL-94 grade test, which means that the addition amount of flame retardant BNGS has no substantial effect on the UL-94 grade.
[0154] The limiting oxygen index test results are shown in Table 2. The limiting oxygen index of UF-BNGS-3 is 27.5%.
[0155] Compared with comparative example 1, coating with UF-BNGS-3 can effectively improve the limiting oxygen index of NW by 26.18%;
[0156] Compared with comparative example 2, it can be seen that when the amount of BNGS added is excessive, the limiting oxygen index of UF will be reduced by 1.09%;
[0157] Compared with Example 1, it can be seen that when the amount of BNGS added is further increased, that is, when the amount of BNGS added is excessive, the limiting oxygen index is significantly reduced by 18.64%, which indicates that excessive addition of BNGS will have a substantial impact on the limiting oxygen index.
[0158] Combined with the SEM test results, it can be seen that adding excessive BNGS will cause protrusions on the coating surface and produce new defects, resulting in the inability to form a dense residual carbon layer, and thus unable to prevent heat and combustible gases from entering the substrate, ultimately leading to a decrease in the limiting oxygen index.
[0159] In order to further quantify the flame retardancy of UF-BNGS-3, cone calorimetry tests were performed. The test results are shown in Figure 6 As shown, the HRR of UF-BNGS-3 reaches 90.03kW / m 2 .
[0160] Compared with comparative example 1, coating UF-BNGS-3 can effectively reduce the HRR of NW by 61.23%;
[0161] Compared with Comparative Example 2, it can be seen that when the amount of BNGS added is high, the effect of reducing HRR is almost negligible;
[0162] Compared with Example 1, it can be seen that when the amount of BNGS added is further increased, that is, when the amount of BNGS added is excessive, the HRR increases significantly, and the increase reaches 56.5%.
[0163] Combining the SEM test results and the limiting oxygen index, the HRR test results also support the above conclusion, that is, when the amount of BNGS added is too much, the flame retardant performance will be reduced.
[0164] The following conclusions can be drawn from Example 1, Comparative Example 4 and Comparative Example 5:
[0165] 1. Applying UF-BNGS-2 flame retardant resin coating can obtain good flame retardant properties;
[0166] 2. The different amounts of BNGS added have no substantial effect on the UL-94 grade;
[0167] 3. Adding a small amount of BNGS can further improve the flame retardant performance, but adding too much BNGS will reduce the flame retardant performance. The reason is that BNGS is a filler. Its flame retardant principle is that adding an appropriate amount of BNGS can effectively fill the defects of the surface flame retardant coating, while adding too much BNGS will cause bulges on the coating surface, showing more defects.
[0168] 4. The amount of BNGS added has a significant effect on the quality of the carbon layer, HRR and residual carbon content formed after combustion. The reason is that the role of UF-BNGS-2 in the technical solution is to promote the formation of a dense structure of the residual carbon layer, significantly increase the residual carbon content, reduce HRR, and achieve the effect of improving flame retardant properties.
Claims
1. A hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating, characterized in that: Hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant BNGS is combined with urea and formaldehyde as main raw materials, dioctyl phthalate DOP is used as plasticizer, and tannic acid TA is used as curing agent. After four stages of reaction, hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating UF-BNGS can be obtained.
2. The hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating according to patent claim 1 is characterized in that: The BNGS is prepared by chemical reaction using hexagonal boron nitride BN, 3,5-diamino-1,2,4-triazole GZ and sodium hexametaphosphate SHMP as bio-based flame retardant ingredients as raw materials; The obtained BNGS contains BN, PNC, POP, P=O, -NH2 and OH.
3. The hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating according to patent claim 1 is characterized in that: The temperature at which the UF-BNGS decomposes to 5% by mass is 228.90±1.10°C, the temperature at which the maximum decomposition rate is reached is 301.47±1.50°C, and the residual carbon content at 800.00°C is 39.95±0.50wt.%; When the addition amount of BNGS is 2wt.%, a dense residual carbon layer is formed.
4. A method for preparing a hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating, characterized in that The following steps are involved: Step 1, preparation of hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant, first, hexagonal boron nitride BN is placed in water, and ultrasonically dispersed under certain conditions to obtain a BN solution, then guanazole GZ is placed in the BN solution, and stirred in a water bath under certain conditions to obtain an amino-functionalized BN-GZ solution, then sodium hexametaphosphate SHMP is placed in the BN-GZ solution, and stirred under certain conditions to obtain a BNGS solution, and after the reaction is completed, the obtained product is filtered, washed, dried, and ground into powder to obtain the hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant BNGS; Step 2, preparation of hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating, first, sodium hydroxide solution is added to formaldehyde solution, the pH value of the solution is adjusted to obtain solution A, and then, under certain conditions, urea, BNGS and other raw materials are added in four stages to prepare urea-formaldehyde resin blended hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating UF-BNGS.
5. The preparation method according to claim 4, characterized in that: In the step 1, the mass ratio of BN, GZ and SHMP is 1:1:2; In the step 1, the ultrasonic condition is that the ultrasonic time is 1h; In step 1, the conditions for water bath stirring are: water bath temperature is 60-70° C., stirring speed is 400-500 rpm, and stirring time is 1-1.5 h; In step 1, the stirring reaction conditions are: the reaction temperature is 90° C. and the reaction time is 3 h; In the step 1, the washing is completed under the condition that the pH of the washing solution is 6-7; the drying conditions are that the drying temperature is 80° C. and the drying time is 24 hours.
6. The preparation method according to claim 4, characterized in that: In the step 2, the mass ratio of the total added amount of BNGS, formaldehyde and urea obtained in step 1 is 2:100:57; In step 2, the condition for preparing solution A is to adjust the pH value of the solution to 8.0-8.5; In step 2, the conditions for adding urea are: a stirring speed of 400-500 rpm and a reaction temperature of 90°C.
7. The preparation method according to claim 4, characterized in that: In step 2, the four stages of adding urea are specifically: Step 2.1 is to add the first stage urea under a certain temperature condition, and continue stirring for a certain stirring time after the addition is completed; Step 2.2 is, under a certain temperature condition, first adding acetic acid solution to adjust the pH value of the solution, then adding the second stage urea, and after the addition is completed, continuing stirring for a certain stirring time until the reaction end point is reached; The endpoint of the second stage reaction is determined by the following sign: a drop of the solution is dropped into 30°C water, and the dropped solution condenses in the water without dispersing; Step 2.3 is to first add sodium hydroxide solution to adjust the pH value under a certain temperature condition, and then add urea from the third stage. After the addition is completed, stir until it becomes viscous to obtain UF; Step 2.4 is to add BNGS to UF and stir it under certain conditions to obtain UF-BNGS.
8. The preparation method according to claim 7, characterized in that: In the step 2.1, the amount of urea added is 64.9% of the total amount of urea, the temperature in step 2.1 is 90° C., and the stirring time is continued for 30 minutes; In the step 2.2, the amount of urea added is 21.6% of the total amount of urea, the pH value of the solution is adjusted to 4.5-5.0, the temperature of step 2.2 is 90° C., and the stirring time is continued for 15 minutes; In the step 2.3, the amount of urea added is 13.3% of the total amount of urea, the pH value of the solution is adjusted to 7.5-8.0, the temperature of step 2.2 is 90° C. when adjusting the pH value, and after the pH value is adjusted, the temperature is adjusted to 70° C., and the stirring time is 30-40 min; In step 2.4, the stirring rate for adding BNGS is 400 rpm, and the stirring temperature is room temperature.
9. A hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating, characterized in that: When used as a flame retardant coating for wood, it has flame retardant properties and can form a continuous and dense residual carbon layer after combustion; in the UL-94 grade test, it passes the UL-94V-0 grade test.
10. A hexagonal boron nitride-guanazole-sodium hexametaphosphate flame retardant resin coating, characterized in that: When used as a wood flame retardant coating, the heat release rate HRR is 55.73±1.25kW / m in the cone calorimetry test. 2 .
Citation Information
Patent Citations
Modified ammonium polyphosphate for improving flame retardant property of fireproof coating and preparation method thereof
CN111349355A
Preparation and application of intumescent halogen-free flame retardant
CN115584059A
Polyion liquid / boron nitride nanosheet composite flame retardant as well as preparation method and application thereof
CN117247601A
Bio-based flame-retardant coating based on PGL as well as preparation method and application of bio-based flame-retardant coating
CN118580739A
Phosphorus-nitrogen-containing aniline oligomer modified boron nitride fireproof anti-corrosion bifunctional coating composition and preparation method thereof
CN118978825A